INVESTIGATION OF MECHANICAL PROPERTIES OF FIBERGLASS PROFILE - and; and (Municipal economy of cities (Technical science), 2013)
Studied the work of fiberglass profiles and bolted connections that profile to determine the properties of fiberglass and connections in the boot process.